Von Willebrand disease and Weibel-Palade bodies - Wang, J. W.; Eikenboom, J. (Hämostaseologie, 2010)
Von Willebrand factor (VWF) is a pivotal haemostatic protein mediating platelet adhesion to injured endothelium and carrying coagulation factor VIII (FVIII) in the circulation to protect it from premature clearance. Apart from the roles in haemostasis, VWF drives the formation of the endothelial cell specific Weibel-Palade bodies (WPBs), which serve as a regulated storage of VWF and other thrombotic and inflammatory factors. Defects in VWF could lead to the bleeding disorder von Willebrand disease (VWD).Extensive studies have shown that several mutations identified in VWD patients cause an intracellular retention of VWF. However, the effects of such mutations on the formation and function of its storage organelle are largely unknown. This review gives an overview on the role of VWF in WPB biogenesis and summarizes the limited data on the WPBs formed by VWD-causing mutant VWF.
Keywords: Weibel-Palade body; von Willebrand factor; von Willebrand disease